Environmental factors are primary determinants of different facets of pond macroinvertebrate alpha and beta diversity in a human-modified landscape. (September 2019) - Hill, Matthew J.; Heino, Jani; White, James C.; Ryves, David B.; Wood, Paul J.
Abstract: Understanding the spatial patterns and environmental drivers of freshwater diversity and community structure is a key challenge in biogeography and conservation biology. However, previous studies have focussed primarily on taxonomic diversity and have largely ignored the phylogenetic and functional facets resulting in an incomplete understanding of the community assembly. Here, we examine the influence of local environmental, hydrological proximity effects, land-use type and spatial structuring on taxonomic, functional and phylogenetic (using taxonomic relatedness as a proxy) alpha and beta diversity (including the turnover and nestedness-resultant components) of pond macroinvertebrate communities. Ninety-five ponds across urban and non-urban land-uses in Leicestershire, UK were examined. Functional and phylogenetic alpha diversity were negatively correlated with species richness. At the alpha scale, functional diversity and taxonomic richness were primarily determined by local environmental factors while phylogenetic alpha diversity was driven by spatial factors. Compositional variation (beta diversity) of the different facets and components of functional and phylogenetic diversity were largely determined by local environmental variables. Pond surface area, dry phase length and macrophyte cover were consistently important predictors of the different facets and components of alpha and beta diversity. Our results suggest that pond management activities aimed at improving biodiversity should focus on improving and/or restoring local environmental conditions. Quantifying alpha and beta diversity of the different biodiversity facets facilitates a more accurate assessment of patterns in diversity and community structure. Integrating taxonomic, phylogenetic and functional diversity into conservation strategies will increase their efficiency and effectiveness, and maximise biodiversity protection in human-modified landscapes. Highlights: Functional and taxonomic alpha diversity were determined by local environmental factors. Functional and phylogenetic beta diversity were determined by local environmental factors. Pond management activities should focus on improving local environmental conditions. Taxonomic, functional and phylogenetic diversity should be integrated into conservation strategies.